Constitutionality of PERPU Number 2 of 2022 Concerning Job Creation Based on the Ruling of the Constitutional Court Number 91/PUU-XVIII/2020 - Negara, Dharma Setiawan; Lufsiana, Lufsiana; Nainggolan, Samuel Dharma Putra (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2023)
Applicability Constitution Number 11 of 2020 concerning Job Creation changes several arrangements previous employment _ arranged in Constitution Number 13 of 2003 Concerning Employment give rise to various polemic in proven implementation _ with he sued Constitution Number 11 of 2020 concerning Job Creation to Court The resulting constitution decision that Constitution the must repair, especially those related with employment. Because of That Government through the President set Regulation Government Replacement Law (PERPU) Number 2 of 2022 concerning Job Creation as an answer to the polemic and emptiness of the law that occurred. Study This is a study law normative with the use approach legislation and approach conceptual study about the constitutionality of PERPU Number 2 of 2022 concerning Job Creation which has been determined by the President Republic of Indonesia. PERPU is made only if a situation is critical. PERPU 2/2022 was created when the Job Creation Law was declared to need to be revised because it was decided by the MK to be in conflict with the Constitution, while the Covid 19 conditions required the state to continue to maintain economic stability, therefore PERPU 2/2022 was issued, however, this PERPU was also challenged by the MK because It is considered that some of the content does not reflect any form of protection for workers. Apart from that, the applicant's argument for a judicial review of PERPU also argued that PERPU 2/2022 was made even though it was not in a critical situation.